Milk it for all its worth - Fritschel, Heidi (International Food Policy Research Institute, 2012)
There are a number of points along the value chain where the quality and safety of milk may be compromised. This figure shows how the quality of milk from one cow in Assam, India, changes as it moves along the value chain to consumers. Along the way, it may be contaminated by bacteria, which can pose a threat to human health, or it may be adulterated with added water, which reduces its nutritional value. This kind of analysis shows exactly where the greatest risk to milk quality is generated, and therefore where along the value chain scarce resources for improving milk quality should be concentrated.